Filsafat Dakwah: Sebuah Upaya Keluar dari Kemelut - Enjang As (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
Preaching as part of the sacred duty of every Muslim is a human effort to do good and leave the evil and do mischief on the earth by strengthening potential Taqwa inspiration and inspiration fujur thus minimize potential human being in the way of the Lord. Therefore, the call can be regarded as the savior of mankind from the shackles of himself and his neighbor. On the basis of this propaganda is seen as a great work done for his fellow human beings, and are aware of work in order to humanize humans.